An investigation into lean practices and their impact on sustainability performance in the latex glove manufacturing industry - Tanushan, S.; Noraini, Mohd Razali (Penerbit UMP, 2021)
Lean is characterized as a collection of management practices. Lean's central philosophy is to minimize and eradicate non-value-adding practices and waste. High quality and customer loyalty are guaranteed by the Lean process. Lean concept obtains its root from Toyota Production system (TPS). The TPS approach is often well suited to high-volume manufacturing. Lean, however, is also applicable in any setting where process waste is encountered. The intent of this study is to develop a lean sustainability performance assessment to analyze the level of lean implementation and its impacts on sustainability performance in Latex Glove Manufacturing Industries. The assessment method is generally in the form of Five-Point Likert Scale Questionnaire which consists of two main sections, Section A, to determine the level of lean practices in the company and Section B to distinguish the impact of the implemented lean practices on sustainability performance in the aspect of social, environmental and economic. Thirty employees from three different Latex Glove Manufacturing Industries (Company A, B, and C) in Selangor were involved in this study. The data was then analyzed using Minitab 15. Among the 22 combined hard and soft lean tools, Just-In-Time (JIT) for hard lean tool and Customer focus for the soft lean tool has scored the highest level of implementation in all three Industries. As for sustainability performance, economic sustainability performance scored the highest average mean score followed by environment and social sustainability performance. Overall, the finding shows that Company A and C have an overall better impact towards sustainability performance by the execution of lean practices as compared to company B. This must be predominantly due to the high level of implementation of soft lean tools as both the companies have a high level of implementation for the majority of the soft lean tools as compared to the implementation of hard lean tools. In conclusion, the higher the level of implementation of lean tools and practices, the greater the impact on it the sustainability performance in a company.